PENERAPAN PIDANA TERHADAP ANGGOTA POLRI YANG MELAKUKAN TINDAK PIDANA PENCURIAN DENGAN KEKERASAN MENGGUNAKAN SENJATA API (Studi Putusan Nomor : 42/Pid.B/2016/PN.Swl dan Putusan Nomor : 43/Pid.B/2016/PN.Swl) - Hendro, Bevi; Faniyah, Iyah; Wibowo, Adhi (Universitas Ekasakti, 2018)
Based on Article 363 paragraph (1) of the 4th Criminal Code, people who commit theft carried out by 2 persons together or more are threatened with a maximum imprisonment of 7 years. Therefore the Case of Crime of Theft with Violence using Firearms based on Decision Number: 42 / Pid.B / 2016 / PN.Swl and Decision Number: 43 / Pid.B / 2016 / PN. 1 (one) year and 10 (ten) months, charge the Defendant to pay a court fee of Rp. 5,000.00 (five thousand rupiah) and pay attention to Article 365 paragraph (2) of the 2nd Book of the Criminal Law. The specification of this research is descriptive analytical. While the approach method used is normative juridical. The data source used is secondary data. The data obtained were analyzed qualitatively and presented descriptively analytically. Based on the results of research and discussion, it can be concluded; First, the application of a criminal against a member of the National Police who commits a crime of theft with violence using firearms in the decision number: 42 / Pid.B / 2016 / PN.Swl and Decision Number: 43 / Pid.B / 2016 / PN.Swl are: Article 365 paragraph (2) of the 2nd Criminal Code, namely: